Analisa Kebutuhan Sistem Informasi Electronic Office pada Kantor Gereja Menggunakan Model System Engineering Life Cycle - Sugiarto, Adrian Herma; Bangkalang, Dwi Hosanna (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2023)
The administration section has an essential role in the church's administrative processes. Administrative staff are required to have an accurate and efficient way of working. In routine tasks, the administrative staff is closely involved in correspondence administration. The mail management system at Gereja Kristen Indonesia (GKI) Tegalrejo Salatiga office still uses the conventional filing system. This causes complex mail monitoring, and many must be following up immediately, making the correspondence administration process ineffective. Therefore, a mail management Electronic Office information system is required to accommodate the needs of business processes in church offices. The software development method used in this research employs the System Engineering Life Cycle model developed by Alexander Kossiakoff with the Concept Development stage. This research resulted in a design of an Electronic Office information system needs with mail management that suits the needs of church offices. The results of this research can be a blueprint to help the process of further Electronic Office software development so the GKI Tegalrejo Salatiga office can implement it to improve correspondence administration services.